Going NUTS: The regional impact of extreme climate events over the medium term - Sehrish Usman; Guzmán González-Torres; Miles Parker (European Central Bank (ECB), 2024)
The projected increase in extreme climate events in the coming decades is likely to exacerbate the existing productivity and demographic challenges facing Europe. We study the dynamic, medium-run macroeconomic effects of heatwaves, droughts and floods in 1160 EU regions through the lens of a local projections, difference in difference framework. Summer heatwaves and droughts lower medium-term output, but the impact from floods depends on regional income levels. High-income regions witness reconstruction activity, less wealthy regions do not. We find evidence of population decline in affected regions as well as adaptation spending post-event, which lowers regional productivity.
Keywords: D24; E24; J22; R11; Q54; 330; xtreme climate; weather; potential output; labour market; productivity; local projections; difference in difference